PROGRAM STUDI LAPANGAN MENINGKATKAN KEMAMPUAN INTERPERSONAL MAHASISWA - Ai Surtika Dewi (Aspirasi Masyarakat, 2024)
The practical program in the field is carried out by the university in order to provide learning to students to find out the work process is associated with the theory learned in college and provides the main benefits in the context of education to improve interpersonal skills in the form of informal interaction, skill development, practical experience and improvement of communication skills. It was carried out in one working day which consisted of a review of the work site at Perum Jasa Tirta II Jatiluhur, listening to the provision of material by the facilitators and discussions. It is hoped that this activity can provide organizational experience for students so that they can improve interpersonal skills in management decision-making.